Penerapan Senam Prolanis Pada Pasien Diabetes Melitus Tipe II Di Puskesmas Lempuing Kota Bengkulu - Maulin Nadinda Syahputri; Darma, Dimas Dewa (Gayaku Publisher, 2024)
Physical activity such as Prolanis exercise in type II diabetes mellitus patients can increase insulin resistance sensitivity to optimize insulin function. Research Objective To determine Prolanis Exercise on Blood Glucose Levels and Peripheral Circulation in Clients with Type II Diabetes Mellitus. Method: The research design is true experimental with pre-test and post-test control group design. The total sample was 36 people consisting of 12 people in intervention group 1, 12 people in intervention group 2 and 12 people in the control group. The sampling technique is simple random sampling. Analysis using Wilxocon and Kruskal Wallish at α < 5%.Research Results shows that the average blood sugar level value after being given the Prolanis Exercise intervention decreased by 57 mg/dl with a p value = 0.004. The average peripheral circulation ABI value after being given the Prolanis exercise intervention increased by 0.09 mmHg with a p value = 0.005. Prolanis exercise has an effect on reducing blood glucose levels and improving peripheral circulation